Emerging Patterns of Collective Action in India’s Platform Economy: A Study of Drivers and Delivery Workers - Chintala, Swati Reddy (Relations industrielles / Industrial Relations, 2023)
Studying collective action in the platform economy against the backdrop of the informal economy in India, I make two arguments that show how work organization in the platform economy enables collective action and distinguishes it from the informal sector. First, I argue that platform work organization through algorithmic work allocation, high employer visibility and algorithmic rather than direct managerial control makes collective action possible. In the informal economy, layers of middlemen often obscure the employment relationship by denying workers a clear contender and the opportunity to develop relationships of solidarity. Second, platform workers address their demands to two targets: the platform company and the state. Informal worker unions have no single, identifiable employer and traditionally confine their demands to the state.SummaryResearch ObjectiveThe objective of this study was to analyze collective action in the platform economy in a context where standard employment relationships are the exception, rather than the rule. To this end, I sought to answer two questions:How is collective action in the platform economy different from what is seen in the informal economy?What factors are responsible for the differences in patterns of collective action?MethodologyThis study is based on the analysis of a subset of 60 interviews from a larger sample of 135 in-depth interviews conducted over 3 years (2018-2021). By sampling for range (Weiss, 1995), I could identify the similarities between platform models and how they lead to shared material conditions. In my sample, 27% of the delivery workers and 52% of the drivers had worked for more than one platform company. I could thus corroborate their narratives of managerial control and information about changing conditions of work.ConclusionsI found that the way work is organized and managed in the platform economy enables collective action by platform ride-hailing and delivery workers in ways not seen among informal workers. Algorithmic allocation of work means that workers are directed by apps to wait for orders or rides at common locations around the city. These shared physical spaces allow workers to meet and communicate with each other in ways not intended by platform companies. Relatedly, companies attempt to increase their visibility, and thus secure new customers, through mandatory use of branded uniforms and equipment by workers. Workers can thus easily recognize each other. Control through company apps rather than direct managerial control also encourages communication between workers as they turn to each other to deal with day-to-day questions and shared concerns. Through WhatsApp groups and physical spaces, workers develop a shared antagonism toward platform companies.With the platform company identified as the de facto employer and target of contention, platform workers can make wage and incentive-based demands, in addition to the advocacy and welfare-based demands traditionally made by informal sector workers.